Analisis Sistem Antrian pada Stasiun Pengisian Bahan Bakar Umum (Studi Kasus: SPBU Batui II) - akinah, Nur irni Nahri; Titong, Fitri Sylvianti; Alhasni, Muh Agil (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the queuing system at SPBU Batui II, located on Jalan Trans Sulawesi, Banggai Regency, focusing on motorcycle fuel service. The applied model is the Multiple Channel Queuing System (M/M/S), used to assess service efficiency based on 30-day observation data and customer perceptions collected through questionnaires. The observations revealed that the average service time is 3.89 minutes, with a facility utilization rate of 90.7%, indicating a near-saturation condition. A simulation with an additional service lane demonstrated a significant decrease in waiting time and the number of customers in the queue. The normality test showed that the service time data followed an approximately normal distribution, supporting the use of parametric statistical analysis. Additionally, over 90% of respondents reported satisfaction with the current service system. The study concludes that increasing the number of service lanes improves system efficiency and that the M/M/S model is effectively applicable to high-traffic fuel station queue management.